Healthcare injustice in patients with sickle cell disease. Issue 2 (6th June 2016) - Ezenwa, Miriam O; Patil, Crystal; Shi, Kevin; Molokie, Robert E
Abstract : Purpose: – The purpose of this paper is to detail experiences that sickle cell disease (SCD) patients associate with healthcare justice and injustice in pain control. Design/methodology/approach: – A content analysis study of open-ended comments written by 31 participants who completed a 20-item healthcare injustice questionnaire-revised twice: once in reference to experiences with doctors and once in reference to experiences with nurses. Findings: – Participants' mean age was 33±10 years; most were African-Americans and women. Themes showed: the four domains of healthcare justice were represented in patients' comments; examples of justice and injustice were provided; specific incidents and interactions with healthcare providers were memorable to patients; and setting was a factor important to healthcare experiences because expectations about services vary by setting. Research limitations/implications: – Patients were self-selected. Future work will include qualitative interviews and focus groups to uncover more details about how patients experience healthcare injustice. Practical implications: – Additional training is needed for SCD providers and about proper management of sickle cell pain; educational modules are also needed that address areas of healthcare injustice by patients. Originality/value: – The authors are the first to report how patients define healthcare justice and injustice. Specific details about memorable SCD patient-provider interactions and pain control are described.